NDive: The story of how logistics and supply chain management could be taught - Reiners, Torsten; Wood, Lincoln; Gregory, S.; Petter, Natasha; Teräs, H.; Chang, Vanessa; Gütl, Christian; Herrington, J. (ASCILITE, 2013)
One major element of supply chain management education is helping learners to grasp the complexity, the challenges, and the efficient management of the multiple dimensions in supply chains. Each decision made can ‘ripple’ through supply chains and have serious repercussions that may include causing millions of dollars in damage or triggering a chain of events that degrade the quality of life for people, society, or the environment. We can teach relevant theory and train learners for some situations that do not require immediate responses. However, we remain disadvantaged by the constraints of time and space; observation of a real supply chain is often unpractical, and lengthy times for transports exceeding any class duration. In this paper, we present the nDiVE project which creates a supply chain story to immerse learners, provide an authentic experience in a realistic environment, and apply traditional and advanced gamification mechanisms to engage and motivate learners.